Pengaruh Promosi dan Kreativitas Produk terhadap Keputusan Pembelian pada Toko Sketsa Variasi di Kamang Tangah, Agam - Elsa Sabrina; Era Sonita (Lembaga Yasin AlSys, 2026)
Promotion and product creativity are important factors influencing consumer purchasing decisions, particularly among micro, small, and medium enterprises (MSMEs) in the creative services sector. Although these two factors have been widely studied, research that specifically analyzes the influence of promotion and product creativity on purchasing decisions in printing and vehicle customization service businesses remains relatively limited. This study aims to analyze the effect of promotion on purchasing decisions, the effect of product creativity on purchasing decisions, and the simultaneous effect of promotion and product creativity on purchasing decisions at Toko Sketsa Variasi in Kamang Tangah, Agam. This study employed a quantitative approach with a causal associative survey design, involving 105 consumers as respondents selected through saturated sampling. Data were collected using a Likert-scale questionnaire that had met validity and reliability tests, and were then analyzed through multiple linear regression with the assistance of IBM SPSS Statistics. The results show that promotion has a positive and significant effect on purchasing decisions, product creativity also has a positive and significant effect on purchasing decisions, and the two variables simultaneously have a significant effect on purchasing decisions, with the ability to explain 50.4% of the variation in purchasing decisions. These findings strengthen the application of the Theory of Planned Behavior in explaining consumer behavior in creative-service MSMEs and broaden the understanding of the role of promotion and product creativity in enhancing purchasing decisions. The conclusion of this study emphasizes that optimizing promotional strategies and strengthening product creativity are important factors in encouraging consumer purchasing decisions. The implications of the study include theoretical contributions to the development of consumer behavior studies and practical implications for MSME actors in optimizing digital marketing-based promotional strategies and improving product creativity to strengthen business competitiveness.